2022
DOI: 10.1177/00223433221099058
|View full text |Cite
|
Sign up to set email alerts
|

National identity, willingness to fight, and collective action

Abstract: Why do people risk their lives fighting in wars? This article looks beyond group grievance and material benefits to add another psychological mechanism explaining why people choose to fight or not to fight – perceived collective action. An individual is much more likely to fight when they perceive that others will also fight. Contrary to the expectations of social identity theory and social pressure theory, the effect of perceived collective action is stronger among those who have a weaker national identity be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
(73 reference statements)
0
4
0
Order By: Relevance
“…‘Balancing’ in the TNSS was notably in terms of cooperating with the USA and Japan to defy China at a time when both Washington and Tokyo were becoming increasingly bold in confronting Beijing across a range of issues, including support for Taiwan. Support for ‘balancing’ in the abstract or in the absence of options for partnerships is unknowable from the TNSS, although other surveys indicate some willingness by the Taiwanese public to resist Chinese aggression alone (Lin, 2018; Wang and Eldemerdash, forthcoming).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…‘Balancing’ in the TNSS was notably in terms of cooperating with the USA and Japan to defy China at a time when both Washington and Tokyo were becoming increasingly bold in confronting Beijing across a range of issues, including support for Taiwan. Support for ‘balancing’ in the abstract or in the absence of options for partnerships is unknowable from the TNSS, although other surveys indicate some willingness by the Taiwanese public to resist Chinese aggression alone (Lin, 2018; Wang and Eldemerdash, forthcoming).…”
Section: Discussionmentioning
confidence: 99%
“…That PRC threats resulted in rising public support for external balancing rather than retaliation or immediate independence indicates a strong status quo preference among the Taiwanese public. Separate experimental survey research about growing support for defending Taiwan in the event of a PRC attack reinforces this impression (Wang and Eldemerdash, forthcoming). These observations imply that political parties have incentives to demonstrate resolve in maintaining Taiwan's de facto independent status and developing defensive capabilities rather than to accommodate Beijing or seek formal independence immediately.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…In this vein, it is important to also pay attention to those with a dual identity, as many citizens might re-identify as both "Taiwanese and Chinese" when reverting from a Taiwanese-only identity. Wang and Eldemerdash (2023) found that compared to citizens who identified as Taiwanese only, those who did not have a solely Taiwanese identity were much more likely to rely on others' behavior to decide their own actions if a war occurred. In the experiment they ran, simply telling this group that 82% of Taiwanese would resist a Chinese invasion rather than 18% increased their willingness to fight by nearly 22%.…”
Section: Identity Age Generation and Conscriptionmentioning
confidence: 99%